Analisis Pengaruh Kompensasi, Motivasi Dan Disiplin Kerja Terhadap Kinerja Aparatur Sipil Negara Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Ponorogo - megawati, maria tri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
Human resources (HR) is one of main keys in achieving organizational goals. Human resources have an important role as a potential activatorfor all organizational activities. The importance of human resources in an organization demands every organization to have qualified and productive employees. The results of this study show that: 1) Compensation has a positive and significant effect on the performance of State Civil Officers in The Demographic and Civil Registry Service of Ponorogo District. 2) Motivation has a positive and significant effect on theperformance ofState Civil Officersin The Demographic and Civil RegistryService of Ponorogo District. 3) Work discipline has a positive and significant effect on the performance of State Civil Officersin The Demographic and Civil RegistryService of Ponorogo District. Variable thathas dominant effect on performance of State Civil Officers in The Demographic and Civil Registry Service of Ponorogo District is work discipline, because this variable has a highest coefficient value.Â Keywords: compensation, motivation, work discipline, state civil officers performance